Horizontal gene transfer contributes to virulence and antibiotic resistance of Vibrio harveyi 345 based on complete genome sequence analysis - Yiqin Deng; Haidong Xu; Youlu Su; Songlin Liu; Liwen Xu; Zhixun Guo; Jinjun Wu; Changhong Cheng; Juan Feng (BMC Genomics, 2019)
Abstract Background Horizontal gene transfer (HGT), which is affected by environmental pollution and climate change, promotes genetic communication, changing bacterial pathogenicity and drug resistance. However, few studies have been conducted on the effect of HGT on the high pathogenicity and drug resistance of the opportunistic pathogen Vibrio harveyi. Results V. harveyi 345 that was multidrug resistant and infected Epinephelus oanceolutus was isolated from a diseased organism in Shenzhen, Southern China, an important and contaminated aquaculture area. Analysis of the entire genome sequence predicted 5678 genes including 487 virulence genes contributing to bacterial pathogenesis and 25 antibiotic-resistance genes (ARGs) contributing to antimicrobial resistance. Five ARGs (tetm, tetb, qnrs, dfra17, and sul2) and one virulence gene (CU052_28670) on the pAQU-type plasmid p345–185, provided direct evidence for HGT. Comparative genome analysis of 31 V. harveyi strains indicated that 217 genes and 7 gene families, including a class C beta-lactamase gene, a virulence-associated protein D gene, and an OmpA family protein gene were specific to strain V. harveyi 345. These genes could contribute to HGT or be horizontally transferred from other bacteria to enhance the virulence or antibiotic resistance of 345. Mobile genetic elements in 71 genomic islands encoding virulence factors for three type III secretion proteins and 13 type VI secretion system proteins, and two incomplete prophage sequences were detected that could be HGT transfer tools. Evaluation of the complete genome of V. harveyi 345 and comparative genomics indicated genomic exchange, especially exchange of pathogenic genes and drug-resistance genes by HGT contributing to pathogenicity and drug resistance. Climate change and continued environmental deterioration are expected to accelerate the HGT of V. harveyi, increasing its pathogenicity and drug resistance. Conclusion This study provides timely information for further analysis of V. harveyi pathogenesis and antimicrobial resistance and developing pollution control measurements for coastal areas.